Immunomodulatory activity and active mechanisms of a low molecular polysaccharide isolated from Lanzhou lily bulbs in RAW264.7 macrophages - Hailian Wei; Yajun Wang; Wenmei Li; Yang Qiu; Cuiping Hua; Yubao Zhang; Zhihong Guo; Zhongkui Xie (Journal of Functional Foods, 2022)
Exploring immunomodulatory effects of polysaccharides mechanisms is highly significant. In this study, Lanzhou lily (Lilium davidii var. unicolor) polysaccharides (LP) of 6.80 × 103 Da were extracted using the freeze-thaw method. For analytical purposes, structure characterization was conducted using fourier transform infrared spectrometer (FTIR), ultraviolet spectrophotometer (UV–Vis), scanning electron microscope (SEM), and transmission electron microscopy (TEM). Results showed that LP exhibited characteristics of polysaccharide functional groups. Moreover, findings on its immune activity showed that LP can stimulate macrophage RAW264.7, promote macrophage proliferation, secrete nitric oxide (NO), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6). We use RNA-Seq to explore how LP mechanisms effect macrophages. Results revealed that LP likely plays an immunomodulatory role through cytokines secretion, cytokines that effectuate G-protein coupled receptor subunits, and activating downstream immune-related signaling pathways. This study can be used as a reference for the further development of LP while also offering an in-depth understanding of mechanistic immunoregulatory activity.